KEANEKARAGAMAN HAYATI TANAMAN LUMUT (BRYOPHITHA) DI HUTAN SEKITAR WADUK KEDUNG BRUBUS KECAMATANPILANG KECENG KABUPATEN MADIUN - Tiara Kusuma Wati; Bekti Kiswardianta; Ani Sulistyarsi (Florea: Jurnal Biologi dan Pembelajarannya)
The aim of research to determine the diversity of plant species of moss in the forest areas Â around the reservoir Kedung Brubus Pilang Kenceng District of Madison County , based on the external structure and taxonomy , as the building blocks of high school biology lab manual mosses ( Bryophyta ) .Teknik research exploration , consisting of 6 points location as a decision mosses around the reservoir Kedung Brubus . Moss plants were found to be observed , identified, noted habitat , research location on the chart observations , documented and made herbarium . The results of the study there are 10 species Leucophanes glaucum, Thiudium investa, Polytrichum commune, Garovaglia plicata, Chenidium lychnites, Meteorium miquelianum, ricissa sp, Pogonotum cirrhatum, Fissidens cristatus, Barbrlla enervis.